Satellite-derived estimation of environmental suitability for malaria vector development in Portugal - Benali, A.
Malaria was endemic in Europe for more than two millennia until its eradication in the 1970s. Recent autochthonous cases registered in Greece have increased the awareness regarding the threat of malaria re-emergence in Southern Europe. Currently, the presence of competent vectors, suitable environmental conditions and the evidences of a changing climate may increase the widespread re-emergence of malaria in Southern Europe.This work focused on determining the current relationships between environmental factors and the density of the former malaria vector Anopheles atroparvus in Portugal, a previously endemic country. Adult females were sampled and vector density was estimated in 22 sites in Southern Portugal between 2001 and 2010 and related with land cover and satellite-derived air temperature and vegetation indices. The relationship between vector density and local larval habitat, temperature and, in a broader sense, to environmental suitability, was assessed using a statistical modelling approach.Results showed that present environmental conditions are suitable for vector development at high densities and the spatial and temporal patterns closely resemble the ones registered in the past endemic period. The use of satellite-derived data, together with statistical models, allowed the extrapolation of suitable environmental conditions for vector development from site-level to the Portuguese mainland territory. This work also improved the baseline knowledge needed to understand the potential impacts of future environmental changes on vector density and, indirectly, on the risk of malaria re-emergence.